Carpal Tunnel Syndrome and Hand-Arm Vibration: A Swedish National Registry Case–Control Study. Issue 3 (6th March 2022) - Vihlborg, Per; Pettersson, Hans; Makdoumi, Karim; Wikström, Sverre; Bryngelsson, Ing-Liss; Selander, Jenny; Graff, Pål
Abstract : The clinical significance of this paper is the statistically significant increased risk for carpal tunnel syndrome due to hand-arm vibration exposure. The highest increased risk was found among younger men. The results show the importance of investigating hand-arm vibration exposure among carpal tunnel syndrome patients. Abstract : Objective: To investigate the increased risk for carpal tunnel syndrome (CTS) in men and women with hand-arm vibration (HAV) exposure. Design: Case–control study of CTS where 4396 cases was obtained from National Outpatient Register between 2005 through 2016. Cases were matched to controls and exposure was estimated using a job exposure matrix. Results: Exposure to HAV increased the risk of CTS with an OR of 1.61 (95% CI 1.46–1.77). The risk was highest in men <30 years of age and among women <30 years no increased risk was observed. The risk increased with a mean year exposure above 2.5 m/s 2 to OR 1.84 (95% CI 1.38–2.46). Conclusions: HAV exposure increase the risk of CTS in both genders, with highest risk increase in younger men. This emphasize identification of HAV exposure in patients with CTS.